OPTIMALISASI MODEL PEMBELAJARAN INOVATIF BERBASIS MASALAH UNTUK PENGUATAN PEMAHAMAN KONSEP SAINS SISWA SEKOLAH DASAR - Cindy; Audy Mita Amelina; Muhammad Sofwan; Febby Ayuni Esya Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science learning in elementary schools plays an important role in developing students’ conceptual understanding and scientific thinking skills from an early age. However, in practice, science learning is still often dominated by conventional teacher-centered methods that are less effective in developing students’ conceptual understanding. Therefore, innovative learning models are needed to encourage students’ active involvement in the learning process. This study aims to analyze the optimization of the Problem Based Learning (PBL) model in strengthening elementary school students’ understanding of science concepts through a literature review approach. The research method used in this study is a Systematic Literature Review (SLR) by analyzing various national and international journal articles published between 2020 and 2026. The literature search was conducted through several academic databases such as Google Scholar, ERIC, and Science Direct using keywords relevant to the research topic. The results of the review indicate that the implementation of Problem Based Learning can improve students’ conceptual understanding of science, critical thinking skills, and learning motivation. In addition, the optimization of PBL implementation can be achieved through the use of contextual problems, effective group discussions, and the utilization of various learning media. Therefore, Problem Based Learning can serve as an effective alternative learning model to improve the quality of science learning in elementary schools.